Training: Google Apps 101 - Yaali, Syarel Azill; Ayob, Mohd Fairullazi (2017)
The objectives of Google Aps 101 Training: •To ensure that the participants are familiar with the software and technology used •To ensure that the participants make use of the apps to make their work goes even smoothly •To ensure that there will be less complaints about "hard disk is full" or PC is slow due to the fact that too many documents are in it.